2022
DOI: 10.1021/acsbiomaterials.2c00051
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Microencapsulation Enhances Cryopreservation of Red Blood Cells with Trehalose

Abstract: Cryopreservation of red blood cells (RBCs) plays a vital role in preserving rare blood and serologic testing, which is essential for clinical transfusion medicine. The main difficulties of the current cryopreservation technique are the high glycerol concentration and the tedious deglycerolization procedure after thawing. In this study, we explored a microencapsulation method for cryopreservation. RBC− hydrogel microcapsules with a diameter of approximately 2.184 ± 0.061 mm were generated by an electrostatic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…ATP concentration is an important parameter of energy source for the overall functioning of RBCs, which is a significant indicator for RBC metabolism. 52,53 The ATP concentration of RBCs after cryoprotection with 4.5% P + 0.6% F was similar to that of the fresh cells (3.67 vs. 3.96 mM). The result indicated that the RBCs, after cryopreservation with the amino acidbased CPAs, can still maintain their physiological function (Fig.…”
Section: Cryopreservation Of Sheep Red Blood Cellsmentioning
confidence: 67%
“…ATP concentration is an important parameter of energy source for the overall functioning of RBCs, which is a significant indicator for RBC metabolism. 52,53 The ATP concentration of RBCs after cryoprotection with 4.5% P + 0.6% F was similar to that of the fresh cells (3.67 vs. 3.96 mM). The result indicated that the RBCs, after cryopreservation with the amino acidbased CPAs, can still maintain their physiological function (Fig.…”
Section: Cryopreservation Of Sheep Red Blood Cellsmentioning
confidence: 67%
“…One‐step and multistep methods are usually utilized to remove CPAs from cryopreserved cells, whose processes often require cell washing and centrifugation 73–75 . For glycerol‐based freezing methods, intracellular glycerol must be washed by the multi‐step method to avoid posttransfusion intravascular hemolysis 76 . After the deglycerolization process, ~15% of the RBCs are hemolyzed, the RBC morphology alters, and there is ~1% Gly residue in the cells 11,77,78 .…”
Section: The Safety Of Cpasmentioning
confidence: 99%
“…[ 49–52 ] Nowadays, to prevent the Leidenfrost effect and improve thermal cooling, simpler tools (e.g., nylon mesh, stainless steel mesh, or medical gauze) were chosen for cryopreservation of a small number of mammalian cells, but they had not yet solved the problem of freezing larger‐volume samples. [ 53–55 ]…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51][52] Nowadays, to prevent the Leidenfrost effect and improve thermal cooling, simpler tools (e.g., nylon mesh, stainless steel mesh, or medical gauze) were chosen for cryopreservation of a small number of mammalian cells, but they had not yet solved the problem of freezing larger-volume samples. [53][54][55] In this study, to provide a feasible and straightforward method for scalable volume cryopreservation of human RBCs, we chose a polytetrafluoroethylene (PTFE) tube as the freezing vessel to stably increase the cooling rate. In addition, we continued to use the fine-tuned trehalose dehydration technique to reduce the glycerol requirement from 17.5% to 5%.…”
Section: Introductionmentioning
confidence: 99%